Analisis Literatur: Peran Inovasi Metode Kolaboratif dalam Meningkatkan Partisipasi Belajar Siswa pada Pembelajaran IPS - Istiqomah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the contribution of innovative collaborative learning methods in enhancing student engagement in Social Studies (IPS) education. Using a qualitative approach through a literature review, this research draws upon academic sources such as journals, books, and relevant articles. The findings indicate that the application of collaborative learning strategies- such as the Jigsaw model, Think Pair Share, and Numbered Heads Together-can create a more dynamic and participatory learning environment. These strategies have been proven to increase student involvement, foster a sense of collective responsibility, and promote the development of critical thinking skills. This review highlights the importance of teacher creativity in adapting collaborative approaches to the learning context in order to foster more effective student participation.